The Hegemony of Patriarchal Culture in Critical Eleven and The Architecture of Love - Jessica Tamara (Institute of Research and Community Outreach - Petra Christian University, 2023)
This article is intended to analyze how patriarchy values are still implemented in Indonesian literature and this it will specifically analyze how Raia and Anya from Ika Natassa’s work called Critical Eleven and The Architecture of Love face the problem with patriarchy culture that is still affecting their attitude when they face the values. This paper will be talking about the theories using 3M masak, macak, manak (cooking, dressing -up, having babies). The thesis will be talking about Raia and Anya who are affected with these norm values around them with their daily life. This article shows how the patriarch values affect both Raia and Anya in their life and how those values are still implemented in Ika Natassa’s book.